2007
DOI: 10.1007/s00381-007-0537-9
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hemorrhages due to late-type vitamin K deficiency bleeding

Abstract: All newborns should receive vitamin K prophylaxis to prevent bleeding due to vitamin K deficiency. Symptoms of any predisposing disease and warning bleeds must be noticed early and additional doses of vitamin K should be administered, if required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Intracranial haemorrhage due to VKDB causes signifi cant mortality and morbidity 3,9,10 . Neurological defi cits including developmental delay, epilepsy, blindness, strabismus, spastic paresis, growth retardation and hydrocephaly have been described in surviving infants 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracranial haemorrhage due to VKDB causes signifi cant mortality and morbidity 3,9,10 . Neurological defi cits including developmental delay, epilepsy, blindness, strabismus, spastic paresis, growth retardation and hydrocephaly have been described in surviving infants 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Authors regard the eff ectiveness oral route inconclusive because most of the studies used biochemical indicators which lack correlation and scientifi c evidence 8 . In view of high burden of VKDB additional dose of vitamin K is suggested for all infants 2,9 . In breast fed infants, infants with liver disease, antibiotic uses and diarrhoea there is defi nitive role of additional doses 10 .…”
mentioning
confidence: 99%
“…Causes of secondary bleeding are believed to originate in dysfunctional absorption of vitamin K. 1,17) This dysfunction is usually attributed to hepatic or intestinal disease, such as biliary atresia, cystic fibrosis, and a 1 -antitrypsin deficiency. In a review of 131 reported cases of late type disease, 55 (42%) were associated with cholestatic disease, 5) including 22 cases of a 1 -antitrypsin deficiency, 11 cases of biliary atresia, and 22 cases involving other forms of liver disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Late type vitamin K deficiency bleeding is the most important, as intracranial hemorrhage (30-60%) can result, leading to high mortality (19.9-50%) and morbidity rates. 1,6,11,12) In contrast, the early and classic types tend to be less common causes of intracranial hemorrhage. Intracranial hemorrhage is observed as subarachnoid hemorrhage (50.0-85.7%), subdural hematoma (48.8-50.0%), intracerebral hemorrhage (42.9-58.3%), or intraventricular hemorrhage (10.7-41.6%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation